Effect of maternal psychopathology on neurodevelopmental outcome and quality of the dyadic relationship in preterm infants: an explorative study. (2nd January 2020) - Pisoni, C.; Spairani, S.; Fauci, F.; Ariaudo, G.; Tzialla, C.; Tinelli, C.; Politi, P.; Balottin, U.; Stronati, M.; Orcesi, S.
Abstract: Background: The literature shows that parents of preterm infants are at risk of psychological distress and that this may impact on the quality of the parent–child relationship and on the child's development. Aim: This longitudinal study was conducted to examine in preterm infants relationships between maternal psychological variables, parental protective factors, perinatal infant variables, and neurodevelopmental outcome. Furthermore, we explored the impact of these variables on the quality of the mother–infant relationship (dyadic synchrony). Subjects and methods: A total of 29 preterm infants (GA < 34 weeks) and their mothers were evaluated twice: at t 0, during the infant's hospitalization in the neonatal intensive care unit (NICU), and at 12 months of infant corrected age (t2). Results: With the exception of decreases in anxiety and perceived social support and an increase in the rate of severe depression at follow-up, there were no significant changes between t 0 and t 1 assessments. The infant's perinatal risk status was the variable that impacted most on maternal psychopathology. Furthermore, our data revealed that baseline maternal stress related to the appearance of the child and to the mother's perception of her parenting role represent a risk factor in relation to developmental outcome at 12 months of corrected age. Finally, no correlations emerged between dyadic synchrony and infant perinatal data, maternal psychological variables (at t 0 and at t 1 ), or child developmental outcome at t 1 . Conclusions: Our results underline the need to identify negative maternal affective states early in the mother–child relationship and to provide mothers with adequate support in the NICU, to enhance their parental role.